The effect of static stretching on phases of sprint performance in elite soccer players - Sayers, A. L.; Farley, R. S.; Fuller, D. K.; Jubenville, C. B.; Caputo, J. L. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to determine which phase of a 30-m sprint (acceleration and/or maximal velocity) was affected by preperformance static stretching. Data were collected from 20 elite female soccer players. On two nonconsecutive days, participants were randomly assigned to either the stretch or no-stretch condition. On the first day, the athletes in the no-stretch condition completed a standard warm-up protocol and then performed three 30-m sprints, with a 2-minute rest between each sprint. The athletes in the stretch condition performed the standard warm-up protocol, completed a stretching routine of the hamstrings, quadriceps, and calf muscles, and then immediately performed three 30-m sprints, also with a 2-minute rest between each sprint. On the second day, the groups were reversed, and identical procedures were followed. One-way repeated-measures analyses of variance revealed a statistically significant difference in acceleration (p < 0.0167), maximal-velocity sprint time (p < 0.0167), and overall sprint time (p < 0.0167) between the stretch and no-stretch conditions. Static stretching before sprinting resulted in slower times in all three performance variables. These findings provide evidence that static stretching exerts a negative effect on sprint performance and should not be included as part of the preparation routine for physical activity that requires sprinting.